Values and Moral Foundations as a Basis for Attitude toward Mentally Retarded People in Students - Oleg A Sychev; Evgeniya M Trofimova (Peoples' Friendship University of Russia (RUDN University), 2018)
An important factor of the successful integration of mentally retarded people is the readiness of the society to accept such people as equal members. In this study we tested the hypothesis that the attitude toward mentally retarded people depends on values and moral factors. The sample comprised 169 students of technical college and pedagogical university. The attitude toward mentally retarded people was measured using a modified version of Mental Retardation Attitude Inventory (MRAI-R by Antonak & Harth), values were tested using Portrait Values Questionnaire (PVQ-R2 by Schwartz), and moral foundations were measured using Moral Foundations Questionnaire (MFQ by Graham et al.). We elaborated modified Russian version of MRAI-R, showed its factor structure and good psychometric properties. The main moral factor of the attitude toward mentally retarded people was the importance of fairness: the higher it is the higher is the readiness to diminish the social distance with the mentally retarded. The importance of authority was associated with the low approval of inclusive education for the mentally retarded. The most important predictor of the attitude toward mentally retarded people was gender: girls demonstrated a more positive attitude towards the mentally retarded.